2011
DOI: 10.1155/2011/215764
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Receptor Agonists and Cardiovascular Events: A Meta-Analysis of Randomized Clinical Trials

Abstract: Objective. Data from randomized clinical trials with metabolic outcomes can be used to address concerns about potential issues of cardiovascular safety for newer drugs for type 2 diabetes. This meta-analysis was designed to assess cardiovascular safety of GLP-1 receptor agonists. Design and Methods. MEDLINE, Embase, and Cochrane databases were searched for randomized trials of GLP-1 receptor agonists (versus placebo or other comparators) with a duration ≥12 weeks, performed in type 2 diabetic patients. Mantel-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 47 publications
3
70
0
1
Order By: Relevance
“…A meta-analysis of 36 trials with a duration ≥12 weeks showed that the MantelHaenszel OR (MH-OR) for major cardiovascular events versus placebo or other comparators was 0.74 for all GLP-1 receptor agonists (95% CI: 0.50-1.08, p = 0.12), 0.85 for exenatide (95% CI: 0.50-1.45, p = 0.55) and 0.69 for liraglutide (95% CI: 0.40-1.22, p = 0.20) [92]. Specifically designed long-term trials are currently assessing the cardiovascular effects of GLP-1 receptor agonists.…”
Section: Cardiovascular Systemmentioning
confidence: 97%
“…A meta-analysis of 36 trials with a duration ≥12 weeks showed that the MantelHaenszel OR (MH-OR) for major cardiovascular events versus placebo or other comparators was 0.74 for all GLP-1 receptor agonists (95% CI: 0.50-1.08, p = 0.12), 0.85 for exenatide (95% CI: 0.50-1.45, p = 0.55) and 0.69 for liraglutide (95% CI: 0.40-1.22, p = 0.20) [92]. Specifically designed long-term trials are currently assessing the cardiovascular effects of GLP-1 receptor agonists.…”
Section: Cardiovascular Systemmentioning
confidence: 97%
“…In a recently updated meta-analysis of 53 trials, DPP-4 inhibitors were associated with a reduced risk of major cardiovascular events (OR = 0.689; 0.528, 0.899; p = 0.006) compared with placebo or other active treatments [39]. Despite positive cardiovascular effects reported with exenatide or liraglutide [16,40], a similar metaanalysis of 36 trials with exenatide and liraglutide showed a similar trend for a reduction in the incidence of major cardiovascular adverse events, although the difference was not significant versus placebo or active comparators (OR = 0.74; 0.50, 1.08; p = 0.12) [41]. Thus, current data do not support a superiority of GLP-1 receptor agonists over DPP-4 inhibitors regarding potential cardiovascular protection.…”
Section: Clinical Outcomesmentioning
confidence: 96%
“…The results exclude, at least in the short term, any increase in CV morbidity and mortality in comparison with placebo or other active drugs. 134,147,148 Besides, placebo-controlled trials have demonstrated that patients treated with GLP-1 RA have a lower incidence of MACE, CV mortality and all-cause mortality.…”
Section: Glucagon-like Peptide-1 Receptor Agonistsmentioning
confidence: 99%